ANALISIS PENGARUH ROA, DER DAN CR TERHADAP RETURN SAHAM PERUSAHAAN SUB SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2021-2023 - Nurfajria, Khodijah; Purwaningrum, Endang; Mirati, R Elly (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
The purpose of this research is to study how return on assets (ROA), debt-to-equity ratio (DER), and current ratio (CR) impact the stock returns of mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The research sample consists of 44 businesses selected through purposive sampling technique based on certain criteria. The data used comes from past stock prices and the company's annual financial statements. The quantitative method of panel data regression, which uses the common effect model (CEM) approach, was used in this study. The results show that DER and CR have no effect and are insignificant to stock returns; on the other hand, ROA partially affects and is significant to stock returns. Simultaneously, the three independent variables have a significant effect on stock returns. The findings provide practical implications for investors and company management on the importance of considering financial indicators when making investment decisions and developing strategies to improve financial performance.